Extending vocabulary the fun way / Ho Chui Chui - Ho, Chui Chui (UiTM Kedah, 2003)
Reading and listening are good ways to acquire a strong vocabulary. However, language teachers can and should play an important role in helping learners to increase their vocabulary store. Unfortunately, not enough emphasis is placed on vocabulary teaching in the language classroom nowadays. Many English language practitioners seem to stress the importance of grammatical knowledge and view the acquisition of vocabulary as incidental. The author feels that the teaching and learning of both structure and lexis are equally important to achieve communicative efficiency. She shares some of her ideas on the use of language activities to build learners' word power in fun and meaningful ways.